A study on hybrid composite coatings: The significance of its surface wettability, dispersibility and thermal degradation performances - Kumar S.S.A.; Ramesh K.; Ramesh S.; Bang L.T. (Elsevier B.V., 2025)
Adverse effects of corrosion due to numerous environmental factors have led researchers to explore new generation of nanomaterials such as metal oxide, graphene and graphene oxide (GO) that possess excellent properties to provide ultimate resistance and protection against corrosion to be incorporated with binder systems made of organic resins. In this investigation, a novel technique was used to employ different loading ratios of TiO2 nanoparticles (0.5-3 wt%) into the acrylic-epoxy polymer matrix with 90:10 wt% (90A:10E) ratio incorporated with 0.5 wt% GO, in order to effectively fabricate GO/TiO2 based hybrid polymer composite coatings. Moreover, 1 wt% polydimethylsiloxane (PDMS) was consistently incorporated in all the coating samples. The samples were then characterized by Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), ultraviolet-visible spectroscopy (UV?vis), water contact angle measurements (WCA), cross-hatch test (CHT), electrochemical impedance spectroscopy (EIS) and field emission scanning electron microscopy (FESEM) respectively. Throughout the immersion time, the EIS studies showed that the corrosion resistant performance was remarkably enhanced by the inclusion of TiO2 nanoparticles over a period of 90 days. At up to the inclusion of 2 wt% TiO2, the obtained FESEM micrographs showed that the TiO2 nanoparticles dispersed uniformly within the GO-based polymeric matrix, hence confirming their superior dispersion, exfoliation and plugging micropore property arising from their laminated structure. The WCA of the GO/TiO2 coatings were observed to increase as the content of TiO2 nanoparticles increased, whereby the highest WCA of 112.5 was exhibited by the 3 wt% of TiO2 coating system. Among the coating systems, the GO/TiO2 (ratio of 0.5:1 wt%) coating system demonstrated optimum impedance modulus values (Z0.01Hz) beyond 1010 cm2. ? 2024 Elsevier B.V.